ANALISIS MOTIVASI BIDAN DALAM MERUJUK PASIEN UNTUK DILAKUKAN TINDAKAN SECTIO CAESAREA DI PPK II BPJS DI WILAYAH KECAMATAN MAKASAR JAKARTA TIMUR TAHUN 2014 - Risza Choirunissa (Universitas Nasional, 2016)
This thesis aimed to get a picture of the motivations of midwife in referring patients for caesarean section at PPK II BPJS in Makasar Subdistrict of East Jakarta in 2014. This research was carried out because there was a tendency that doctors had cooperation with midwives, so that caesarean section had to be performed at a specific place. The study was a descriptive study with case study design, using in-depth interviews. The informants of the study were : midwives who refered to PPK II BPJS in the Makasar Subdistrict, Head of Public Relation of PPK II, BPJS doctors, patients of private practice midwives (BPS). This study examined factors contributing the motivation of midwives in referring patients for caesarean section at PPK II BPJS based on three factors: environmental conditions, partnerships and benefits.Short distance between the hospital and private practice midwives could facilitate referral patients. Midwives had more confidence about the safety of their patients when referring to PPK II that had complete facilities. BPJS’policy also affected referral patterns for caesarean section at PPK II because the midwives who not become PPK I, they could not refer patients to PPK II directly. Some of midwives only refered to the obstetricians and gynecologists at PPK II that already had existed cooperation with the midwives. Midwives informants reported that they only refered patients with medical indications and not based on or motivated by financial rewards from the reffered. If the referring process was rewarded, then it was just a bonus and not the main goal.In addition, the informants said that the socialization of BPJS program was not adequate in the community. It was expected the provision of services at the BPJS hospital had hospital accreditation certificate. This study suggested that hospital not give rewards to the midwives for refering patients for caesarean section at PPK II. It was also advisable to midwifery professional association to have clear rules and regulation on the referring process and associated financial rewards.